The battle of question formats: a comparative study of retrieval practice using very short answer questions and multiple choice questions - Elise V. van Wijk; Mario de Jonge; Floris M. van Blankenstein; Roemer J. Janse; Alexandra M.J. Langers (BMC Medical Education)
Abstract Background Retrieval practice is a highly effective learning strategy that enhances long-term retention by encouraging the active recall of information. However, the optimal question format for maximizing knowledge retention remains uncertain. In this study, we compared the effect of very short answer (VSAQ) versus multiple-choice question (MCQ) practice tests on students’ knowledge retention. By analyzing these two formats, we aim to identify the most effective approach to retrieval practice, thereby helping to optimize its implementation and improve learning outcomes. Methods In this randomized within-subjects study, students (n = 45) practiced with both VSAQs and MCQs in an extracurricular lifestyle course, without receiving feedback. The final retention test consisted of identical questions in both formats. A 2 × 2 repeated measures ANOVA was used to determine the effect of question format in practice testing and final test on final test score. Additionally, digital questionnaires were used to explore students’ test-taking experiences. Results The VSAQs were answered incorrectly more frequently on the practice tests and final test. There was no main effect of practice question format on final test performance, and no interaction effect between question format on the practice and final test. Regardless of question format, most students thought the practice tests were beneficial for learning. Conclusions We found no evidence indicating that either MCQ or VSAQ is more effective for knowledge retention during retrieval practice. The lower initial retrieval success in the VSAQs, indicated by the higher degree of incorrect answers on the practice tests, might have limited their effectiveness during retrieval practice. To optimize the use of VSAQs in retrieval practice, it seems important to improve initial retrieval success to maximize learning outcomes. Clinical trial number Not applicable.